Simplification of Linear Beam-Forming Networks by Applying a Novel Phase Interpolation Technique - Elizvan Juarez; Marco A. Panduro; David H. Covarrubias; Alberto Reyna (IEEE Open Journal of Antennas and Propagation)
This paper presents a new design proposal for the simplification of linear beam-forming networks by applying a novel phase interpolation technique. This paper proposes the strategic utilization of 1-to-3 division nodes and 2-to-1 recombination nodes to reconstructing the cophasal values necessary for radiation beam scanning in linear phased array systems. This novel technique simplifies the beam-forming network, achieving a reduction of phase shifters by up to 60% and ±18° of scan angle. These benefits are obtained using uniform amplitude excitation and without additional amplitude controls. The complete antenna system considers a broadband V-slot as antenna element for obtaining a bandwidth performance of approximately 1.2 GHz. This results in a 22% of bandwidth. This is illustrated by using a prototype with experimental measurement results and simulations based on electromagnetic solver (CST Microwave Studio). These results reveal an interesting reduction of phase shifters for a good trade-off of beam-steering range and bandwidth behavior. The experimental results are analyzed and compared with other techniques and previous works cited in the literature. This novel methodology provides interesting results of a high benefit for wireless applications of phased antenna systems.